INTERLEUKIN-4 DAN INTERFERON GAMMA DI NEFRITIS LUPUS: HUBUNGAN AKTIVITAS PENYAKIT SERTA KEKAMBUHAN - Torajasa Achamar; Dany Farida; Hani Susianti; Kusworini Handono; Ati Rastini; R.I R.I; I Putu A.S; Atma Gunawan; Handono Kalim (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
Sampling for urinalysis to see the activity and the degree of recurrence of Lupus Nephritis (LN) is very difficult. New biomarkersthat are more simple, sensitive, specific and non-invasive in assessing the activity of the LN need to be investigated. Interleukin-4 (IL-4)and interferon gamma (IFN-γ) were implicated to LN process. Urine samples from 17 LN patients were taken every month for 6 (six)months to examine the level of uIL-4, uIFN-γ, activity and recurrence of LN. Significant differences were observed in the uIFN-γ levelsbetween the active and inactive LN groups (p=0.012), but not in uIL-4 levels (p=0.187). Correlations between each biomarker andrenal domain score were weak (r=0.201, p=0.042 for uIL-4; r=0.268, p=0.006 for uIFN-γ). Significant differences were also found inthe uIL-4 and uIFN-γ levels against LN recurrence (p=0.033; p=0.017). The best cut off values to assess recurrences and activity of LNwere 8.17 pg/mL for uIL-4 showed a sensitivity of 74%, specificity 71%, NPV 90%, PPV 42% to assess recurrences and to assess activityof LN showed sensitivity 46%, specificity 75%, NPV 48%, PPV 78%. The cut off 18.58 pg/mL for uIFN-γ to predict recurrent and assessthe activity of LN showed sensitivity 68%%, specificity 70%, NPV 88%, PPV 40% to predict the recurrent and to assess the activity of LNshowed sensitivity 57%, specificity 64%, NPV 49%, PPV 73%. Based on the research, uIL-4 and uIFN-γ are not good enough to predictrecurrence and activity of LN